2018
DOI: 10.20867/thm.24.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Review of Optimism, Creativity, and Spirituality in Tourism Research

Abstract: Purpose -Optimism, creativity, and spirituality are important variables in Positive Psychology that can lead to better lives. The authors believe these are also fundamental concepts that can bring a new understanding of the tourism experiences, particularly in the current trend of the 'experience economy'. The study aimed to explore optimism, creativity, and spirituality from a Positive Psychology perspective on tourism settings to deepen the understanding of the state of the art and develop ideas for improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The PRISMA checklist (PRISMA, 2019a) sets out the steps that should be followed to carry out a review that is replicable by other researchers and generate trustworthy data. The PRISMA methodology has been adapted for use in tourism research in several publications (Garcês et al, 2018; Stone & Duffy, 2015; Wijesinghe et al, 2017; Yang et al, 2017). Kim et al (2018) contended that a systematic review in tourism against the PRISMA checklist would contribute to having a clearer understanding of the execution, quality, and rigor of systematic reviews.…”
Section: Methodsmentioning
confidence: 99%
“…The PRISMA checklist (PRISMA, 2019a) sets out the steps that should be followed to carry out a review that is replicable by other researchers and generate trustworthy data. The PRISMA methodology has been adapted for use in tourism research in several publications (Garcês et al, 2018; Stone & Duffy, 2015; Wijesinghe et al, 2017; Yang et al, 2017). Kim et al (2018) contended that a systematic review in tourism against the PRISMA checklist would contribute to having a clearer understanding of the execution, quality, and rigor of systematic reviews.…”
Section: Methodsmentioning
confidence: 99%
“…A small group of theoretical contributions addressed creativity in the context of tourism, such as the conceptual development of creative spaces, creative spectacles and creative tourism as an alternative to conventional cultural tourism (Richards and Wilson, 2006). Garcês et al (2018) suggested that creativity in tourism is mainly explored as a background for tourism development through organizational, structural and product innovation development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Optimism is thought to help tourists cope with unexpected events in tourism (Garcês et al, 2018). It is also an important factor in sustainable medical tourism practices in ensuring that behavioural intent is supported with a positive perspective of the patient.…”
Section: Optimism and Pessimismmentioning
confidence: 99%